The Addams family : the complete third volume [videorecording (DVD)] - Addams, Charles, 1912-1988 (MGM DVD., 2009)
Brace yourself for more macabre mayhem and monstrous madness as television's creepiest clan wreaks hilarious havoc on their unsuspecting victims. This time, love is in the air, and it seems that everyone--Pugsley, Ophelia, Uncle Fester, and even Lurch--is being bitten by the bug. Gomez, meanwhile, is burglarizing houses in his sleep, and it's curtains for the new neighbors when Morticia tries her hand at decorating.